Blocos: vozes e percursos da reestruturação do Carnaval de rua no Rio de Janeiro - Barros, Maria Teresa Guilhon M. de (2013)
The focus of this work is the design creation and development of a prototype virtual space that gathers and organize s information about the Street C arnival in Rio. The Carnival celebration in the streets of Rio de Janeiro, despite being an old tradition of the city, went trough a process of expansion and restructuring, during the past twenty years, coming to the present day, in which the party mobilizes millions of revelers. The contemporary gropu s were founded in the mid 1980s, and than shared symbols and values related to identity Rio, the Brazilianness and cultural resistance, dealing with a world of enormous wealth, which speaks directly to the urban development and the political context, and touches issues such as globalization, consumption, circulation, social inclusion, citizenship, among others. Register the memory of that moment of rediscovery and contribute to raising research sources connected to this 'new' Street Carnival, were the mai n motivations for research.